Influence of vertical earthquake on the variations of axial load ratio of reinforced concrete buildings - Awang @ Abdul Halim Taib (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
The objective of this study are to evaluate the variation of axial load of RC building under horizontal earthquake only and vertical and horizontal earthquake; to assess the effect of vertival earthquake on the axial load variation in irregular and regular RC buildings; and to assess the effect of repeated earthquake with vertical component on the axial load variation in irregular and regular RC buildings.